Mass Multiplication of Jatropha curcas L. through Micropropagation - Thakur, Sanket K.; Shukla, Shiv Kant (Indian Journal of Agroforestry, 2020)
The economic importance of J. curcas has increased recently due to its use as bio-diesel producing crop. Plantation of J. curcas has been envisaged in various developing countries to produce bio-diesel. Demand of elite quality planting material of Jatropha is increasing and mass multiplication of elite clone is possible through micropropagation. A series of experiments were conducted to develop protocol for this purpose. Findings of the Â experiments suggest that axillary buds from fresh shoots are ideal explant for initiation of cultures. MS medium supplemented with BAP (1 mg/I), IAA (1 mg/I), adenine sulfate (10 mg/I) and citric acid (30 mg/I) found suitable for shoot multiplication and elongation. Shoots were rooted on half strength MS medium supplemented with NAA (3 mg/I)+ IBA (1 mg/I) + charcoal (250 mg/I). However, success in rooting of shoots was limited (65%). Performance of plants raised through tissue culture were very encouraging as they plants attained a height of 8feet and started bearing fruits after 5 months of planting.